Analisis Dan Perancangan Sistem Informasi Administrasi Pembayaran Biaya Pendidikan Berbasis Web Dan SMS Gateway Pada Pondok Pesantren Al-Anwar Petanang - Febriansyah, Ridho; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2021)
From the information system of the payment administration fee education that runs current payment information is only conveyed to students, then students convey to their parents or guardian and the obstacles most often felt are difficulties Interms of recording and reporting to the leadership and the search for students ' payment data takes a long time because the payment data is recorded in a book so that the officer must search the data one by one. Based on the problems above, the author proposed a payment system for Web-based education and SMS gateways at PondokPesantren Al-Anwar Petanang that can assist in providing solutions to the problems that occur. In this research, the author uses a Unified Modelling Language (UML) modeling tool. This research resulted in a prototype that can be further implemented so as to generate the administrative information system of payment fees for Web-based education and SMS gateways at PondokPesantren Al-Anwar Petanang.